Optimum wavelength of spaceborne oceanic lidar in penetration depth. (November 2020) - Liu, Qun; Liu, Dong; Zhu, Xiaolei; Zhou, Yudi; Le, Chengfeng; Mao, Zhihua; Bai, Jian; Bi, Decang; Chen, Peng; Chen, Weibiao; Liu, Chong
Highlights: The global distribution of ocean penetration depth and the corresponding optimum wavelength bands are calculated for spaceborne photon-counting oceanic lidar. Wavelength bands of 488 nm and 443 nm have good penetration ability and by taking advantage of the characteristic of solar Fe Fraunhoferline (438.355 nm) and H-β Fraunhoferline (486.134 nm), the background light can be suppressed and the penetration depth can be further increased. Wavelength of 486.134 nm is the optimum wavelength of single-wavelength lidar and the combination of 486.134 nm and 438.355 nm is a good choice for dual-wavelength lidar for purpose of global ocean detection. Abstract: The evaluation of the wavelength parameters of spaceborne oceanic lidar is of great importance to ensure that the lidar system can provide more information of ocean and can be realized in engineering. In this paper, the optimum wavelengths of spaceborne oceanic lidar for purposes of ocean detection at coastal and global scales are analyzed mainly in terms of the penetration depth. The global distribution of ocean penetration depth and the corresponding optimum wavelength bands are calculated by using the oceanic optical properties data from Moderate Resolution Imaging Spectroradiometer (MODIS). Ocean with optimum penetration wavelength of 488 nm covers 61.82% of the global ocean and the optimum wavelength of 443 nm with ocean area share of 14.81% is a good complement for 488 nm. The penetration depths of 96.26% of the global ocean are deeper than 0.8 times the euphotic zone depths by using wavelengths of 488 nm and 443 nm, simultaneously. More importantly, taking advantage of the characteristic of solar Fe Fraunhoferline (438.355 nm) and H- β Fraunhoferline (486.134 nm), 70% of the background light can be suppressed by a filter with bandwidth of 0.1 nm and the penetration depth can be increased by approximately 5.0%. In conclusion, we propose that 486.134 nm is the optimum wavelength of single-wavelength spaceborne oceanic lidar and the combination of 486.134 nm and 438.355 nm is a good choice for dual-wavelength lidar for purpose of global ocean detection.